Analýza lesních porostů na vulkánu Hallasan: zhodnocení vlivu disturbancí a kompetice na růst a přežívání stromových populací na gradientu nadmořské výšky. - Altman, Jan (Jihočeská univerzita, 2009)
The study was conducted on Mt. Hallasan (1950 a.s.l.) in South Korea. Forest plots were established along altitudinal gradient (950-1770 a.s.l.) from oak-hornbeam (Quercus serrata, C. laxiflora), to mixed-oak (Quercus mongolica, Taxus cuspidata), and fir (Abies koreana, Sorbus commixta) forests. Vascular plants were identified to species, and their total cover and covers of individual species in herb (> 1 m), shrub (1 - 5 m) and tree (< 5 m) layers estimated using Braun-Blanquet scale. Dentrended Correspondence Analyses was used to analyze relationship between environment and species composition, lifeforms spectra and plant diversity. The spatio-temporal variations in stem dispersion, radial growth, and mode of competition among trees were examined using the mapped location of trees and tree-rings. Changes in radial-growth were used to analyse stand disturbance history using 36647 measured tree-rings. Histories of radial-growth of individuals trees were further examined using visual classification to 5 different groups of growth trends. Ripley´s K-function was used to determine whether the spatial distribution pattern of trees was random, regular or clumped. Spatial size autocorrelations were used to determine the mode and extant of neighbor interactions. Spatial associations of different groups of trees and random mortality test were also computed for tree stands where Abies koreana was a dominant species.
The analysis of forest vegetation on the Hallasan volcano: evaluation of impact of disturbances and competition on growth and survival of tree populations along altitudinal gradient
Analýza lesních porostů na vulkánu Hallasan: zhodnocení vlivu disturbancí a kompetice na růst a přežívání stromových populací na gradientu nadmořské výšky.
Keywords: K-funkce; disturbance; výškový gradient; K-funkce; disturbance; výškový gradient